2019
DOI: 10.1016/j.compbiomed.2018.12.016
|View full text |Cite
|
Sign up to set email alerts
|

High throughput automated detection of axial malformations in Medaka embryo

Abstract: Fish embryo models are widely used as screening tools to assess the efficacy and /or toxicity of chemicals. This assessment involves the analysis of embryos morphological abnormalities. In this article, we propose a multi-scale pipeline to allow automated classification of fish embryos (Medaka: Oryzias latipes) based on the presence or absence of spine malformations. The proposed pipeline relies on the acquisition of fish embryo 2D images, on feature extraction based on mathematical morphology operators and on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…So far, there have been a few studies that focused on the analysis of zebrafish phenotypes using different tools. ,,,,, One of the earliest studies used support vector machine (SVM) to extract image descriptors to recognize three basic zebrafish embryonic phenotypes, i.e., hatched, unhatched, and dead . The ability for abnormal phenotype recognition was limited due to the lack of data set of representing phenotypes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…So far, there have been a few studies that focused on the analysis of zebrafish phenotypes using different tools. ,,,,, One of the earliest studies used support vector machine (SVM) to extract image descriptors to recognize three basic zebrafish embryonic phenotypes, i.e., hatched, unhatched, and dead . The ability for abnormal phenotype recognition was limited due to the lack of data set of representing phenotypes.…”
Section: Resultsmentioning
confidence: 99%
“…With the continuous development of computer vision tools, Random Forrest (RF) classifiers were used to segment the contours of the swim bladder and generate spine curves to determine the developmental stages or abnormalities such as USB and spine deformation. Extremely Randomized Trees were used to differentiate individual phenotypes including normal, dead, chorion, up/down curved tail, up curved fish, short tail, hemostasis, necrosed yolk sac, and edema. ,, The DLMA workflow developed in this study demonstrated the ability to both qualitatively and quantitatively perform zebrafish larvae phenotyping. By working together with the research community to gather diverse zebrafish images, we envisage that a comprehensive model to analyze a variety of parameters in zebrafish larvae at different developmental stages could be achieved for high throughput screening in the near future.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also observe a high specificity of 96% and an acceptable sensitivity of 90%, which suggests that the use of this method is accurate for the global screening test that is to be developed. Indeed, the swim bladder detection assay is intended to be a part of a series of morphological abnormalities detection assays whose each specificity needs to be maximized in order to maximize the accuracy of the whole detection assay and not eliminate a too important number of chemicals [11,27]. The sensitivity of each individual test is expected to improve the sensitivity of the whole test.…”
Section: Classification Results and Discussionmentioning
confidence: 99%